The Impact of the Transformation to the Digital Economy on the Small and Medium Enterprises Sector in the Kingdom of Saudi Arabia: Opportunities and Challenges (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to analyze the impact of the transformation to the digital economy on the small and medium-sized enterprises (SMEs) sector in the Kingdom of Saudi Arabia, focusing on the opportunities and challenges facing this vital sector. The study followed a descriptive-analytical approach, using questionnaires to collect data from a representative sample of 156 participants, including owners and managers of these enterprises. The results revealed that the digital economy significantly contributes to expanding companies' access to global markets, improving the quality of services provided, and supporting more accurate and effective decision-making within enterprises. The study also highlighted key challenges such as the lack of digital skills, the costs of digital transformation, and cybersecurity risks, in addition to the need for greater government support and specialized training programs. Based on these findings, the study recommends strengthening digital training and qualification programs, providing financial support and incentives, developing digital infrastructure, improving regulatory and legislative frameworks, encouraging public-private partnerships, and raising awareness of the importance of the digital economy. These recommendations aim to enable small and medium-sized enterprises (SMEs) to capitalize on digital opportunities and achieve sustainable growth in line with Saudi Vision 2030.
Keywords: Digital Economy; SMEs; Digital Transformation; Service Quality; Global Markets; Digital Skills; Government Support